On the Question of Estimation of Managerial Influence - M. V. Samosudov (Управление)
The article discusses a methodological approach to the estimation of managerial influence. This approach is based on calculating of human behavior vector, involves consideration of the impact of the institutional environment and, consequently, allows to estimate the managerial influence more accurately.